The Contact And Cohesion Theory: A Conceptual Framework Based On The Eastern Context Of Communication - Sarwari, Abdul Qahar (Universiti Putra Malaysia Press, 2017)
Communication is among the main elements and requirements of modern life for all human beings. Communication competence and communication theories help and guide individuals to conduct proper communication and assess the process of interactions among different people. So far, almost all communication theories are developed based on the Western social, cultural and communicative norms, which may not cover works on communications among people in the Eastern parts of the world. This study reviewed and assessed 100 available works on interpersonal communication and intercultural communication from different perspectives. This study also assessed the results of four different original studies on interpersonal communication and intercultural among universities from different social and cultural backgrounds. Through the review of previous works which were available in the literature that mostly belonged the Western parts of the worl d , and thorough the evaluation of the results from the original studies which were conducted in an Asian country, some differences were found based on the main elements and steps of communication . Through the comparison of the results from the reviewed wo rks and from the original studies, this study suggests a new theoretical framework of direct communication among individuals from different backgrounds under the Eastern context of communication. This study suggest the contact initiation, negotiation, cogn ition, and cohesion as four of the main steps for conducting successful interactions among people from different backgrounds based on the Eastern communication norms and social perspectives .